Optimization of the relation of ω-6 / ω-3 fatty acids in sunflower oil - Osyp, Yyriy; Osyp, Maria; Rakovets, Oksana (ScienceRise: Biological Science, 2019)
According to the modern theory of nutrition, food must not only meet the physiological needs of man, but also have therapeutic and prophylactic properties. The disadvantage of sunflower oil is the practical absence of linolenic acid, which is attributed to the group of polyunsaturated fatty acids ω-3 (vitamin F), in its fatty acid composition The enrichment of sunflower oil with linolenic acid transforms it into a product of prophylactic and therapeutic purpose, increasing the number of its functional properties. Purpose of the study: to obtain model mixtures with the optimum ratio of unsaturated fatty acids. Materials and methods: blending method, high-performance gas chromatography method. Results: The fatty acid composition of the obtained fat mixtures was investigated and the ratio of ω-3 / ω-6 polyunsaturated higher carboxylic acids was established, which justifies the use of 90:10 sunflower oil flax blends for daily nutrition and 70:30 for prophylaxis. Conclusions: The results obtained can be used to improve the ratio of higher carboxylic acids ω-3 and ω-6 in the diet, which can have a positive effect on the dynamics of cardiovascular disease. Oil mixtures with a balanced fatty acid composition can become an effective tool for the prevention of cardiovascular diseases and increase the functionality of products of the oil and fat industry